Targeting of Janus kinases limits pro-inflammatory but also immunosuppressive circuits in the crosstalk between synovial fibroblasts and lymphocytes - Yao, Nina; Tretter, Theresa; Kvacskay, Peter; Merkt, Wolfgang; Blank, Norbert; Lorenz, Hanns-Martin; Tykocinski, Lars-Oliver (Biomedicines, 2021)
Crosstalk between synovial fibroblasts (SF) and immune cells plays a central role in the development of rheumatoid arthritis (RA). Janus kinase inhibitors (JAKi) have proven efficacy in the treatment of RA, although clinical responses are heterogeneous. Currently, little is known regarding how JAKi affect pro- and anti-inflammatory circuits in the bidirectional interplay between SF and immune cells. Here, we examined the effects of tofacitinib, baricitinib and upadacitinib on crosstalk between SF and T or B lymphocytes in vitro and compared them with those of biologic disease modifying anti-rheumatic drugs (bDMARDs). JAKi dose-dependently suppressed cytokine secretion of T helper (Th) cells and decreased interleukin (IL)-6 and matrix metalloproteinase (MMP)3 secretion of SF stimulated by Th cells. Importantly, JAK inhibition attenuated the enhanced memory response of chronically stimulated SF. Vice versa, JAKi reduced the indoleamine-2,3-dioxygenase (IDO)1-mediated suppression of T cell-proliferation by SF. Remarkably, certain bDMARDs were as efficient as JAKi in suppressing the IL-6 and MMP3 secretion of SF stimulated by Th (adalimumab, secukinumab) or B cells (canakinumab) and combining bDMARDs with JAKi had synergistic effects. In conclusion, JAKi limit pro-inflammatory circuits in the crosstalk between SF and lymphocytes; however, they also weaken the immunosuppressive functions of SF. Both effects were dose-dependent and may contribute to heterogeneity in clinical response to treatment.
Gesehen am 01.12.2021